The Role of Cystatin C in the Prediction of Contrast-Induced Acute Kidney Injury Following Coronary Procedures: A Systematic Review - Azad Mojahedi; Andreas P. Kalogeropoulos; On Chen; Hal Skopicki (Reviews in Cardiovascular Medicine)
Background: Contrast-induced acute kidney injury (CI-AKI) represents a significant cause of acute kidney injury (AKI) and accounts for 11% of all cases. Conventional biomarkers, such as serum creatinine (SCr), present limitations in terms of sensitivity and specificity for the early detection of CI-AKI. Therefore, this review examines the potential of cystatin C (CysC) as a biomarker for predicting CI-AKI in patients undergoing coronary procedures and assesses its effectiveness compared to traditional markers. Methods: This systematic review was conducted using PubMed to identify studies published between January 2020 and March 2025. The inclusion criteria focused on original studies examining CysC levels for early CI-AKI detection in patients undergoing coronary angiography (CAG) or percutaneous coronary intervention (PCI). Data extraction followed a standardized charting method, focusing on key findings from the selected studies. Results: A total of 7 studies met the inclusion criteria from an initial pool of 410 articles, with data extracted from these seven prospective studies. Key findings indicated that elevated preoperative CysC levels correlated with a higher risk of developing CI-AKI, demonstrating greater sensitivity and specificity than the conventional SCr biomarker. The mean cut-off values for CysC varied across studies, but consistent trends highlighted its potential as an early indicator of renal dysfunction. Conclusions: CysC appears to be a more sensitive biomarker than SCr for the early detection of CI-AKI. This review suggests that integrating CysC measurement into clinical practice could enhance the early diagnosis and management of CI-AKI, ultimately improving patient outcomes. Hence, future research should focus on standardizing CysC cut-off values and further explore their implications in broader clinical settings and guidelines.